Single-dose administration of a short-acting gonadotropin-releasing hormone agonist does not affect cycle outcome in frozen–thawed embryo transfer cycles. Issue 5 (May 2021) - Wang, Hanbi; Tang, Xian; Bukulmez, Orhan; Deng, Chengyan; Yu, Qi; Zhou, Yuanzheng; Sun, Zhengyi; Zhen, Jingran; Wang, Xue; Liu, Meizhi
Objective: This prospective study aimed to assess the effect of short-acting gonadotropin-releasing hormone agonist (GnRHa) administration on pregnancy outcomes in frozen–thawed embryo transfer (FET) cycles. Methods: Patients who planned to have FET in Peking Union Medical College Hospital (China) were recruited for this study and randomly assigned into two groups. Patients in the experimental group (n = 460) received triptorelin acetate on the day of embryo transfer along with routine luteal support. Patients in the control group (n = 433) only received luteal support. One dose (0.1 mg) of a short-acting GnRHa was administered on the day of blastocyte transfer. The rates for clinical pregnancy, biochemical pregnancy, implantation, miscarriage, and ectopic pregnancy were compared between the groups. Results: There were no significant differences in the number and quality of blastocytes transferred between the two groups. In the experimental and control groups, the clinical pregnancy rate was 56.3% and 50.58%, the biochemical pregnancy rate was 15.78% and 18.94%, and the median implantation rate was 39.98% and 38.01%, respectively, with no significant difference between the groups. Biochemical pregnancy and abortion and the ectopic pregnancy rate were not significantly different between the two groups. Conclusion: In FET cycles, a GnRHa does not affect the pregnancy outcome.